Fast and green microwave-assisted digestion with diluted nitric acid and hydrogen peroxide and subsequent determination of elemental composition in brown and white rice by ICP-MS and ICP-OES. (1st January 2023) - Lee, Jian; Park, Ye-Seul; Lee, Do Yup
Abstract: For the elemental determination of rice, a microwave-assisted sample preparation method employing diluted HNO3 and H2O2 under high temperature and pressure was developed in a rapid and eco-friendly manner. The analysis was performed using inductively coupled plasma mass spectrometry (ICP-MS) and inductively coupled plasma optical emission spectrometry (ICP-OES). At 280 °C and 160 bar, the optimal condition for microwave-assisted wet digestion in a single reaction chamber was achieved with a mixture consisting of 3 mL of 0.1 mol L −1 HNO3 and 5 mL of 30% H2 O2 (0.25 g rice sample). The optimized procedure yielded a low residual acidity (RA) of 0.017 mol L −1 and low residual carbon content (RCC) of 355 mg L −1 . The limits of detection (LODs) were from 0.159 (Sb) to 9.863 (Fe) μg kg −1 . Additionally, the developed method received a total score of 85 on the analytical Eco-Scale, indicating an excellent green analysis method. Furthermore, the method was validated by determining 19 elements (Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Ni, P, Pb, S, Sb, Se, and Zn) in brown and white rice cultivated in South Korea. Graphical abstract: Image 1 Highlights: A microwave-assisted digestion method was developed for elemental analysis of rice. The digestion solvent was optimized as 3 mL of 0.1 mol L −1 HNO3 and 5 mL of 30% H2 O2 . The optimal procedure provided low residual carbon content and residual acidity. The developed method was an excellent green analysis method by analytical Eco-Scale. 19 elements were determined in brown and white rice by ICP-MS and ICP-OES.